An immunoinformatic investigation on Rift Valley fever virus protein reveals possible epitopes for vaccines - Tanjir Hosen; Saaimatul Huq; Mohammad Abdullah-Al-Shoeb; Shahidul Islam; Muhammad Abul Kalam Azad (Journal of Infection in Developing Countries)
Introduction: This immunoinformatic study identified potential epitopes from the envelopment polyprotein (Gn/Gc) of Rift Valley fever virus (RVFV), a pathogenic virus causing severe fever in humans and livestock. Effective vaccination is crucial for controlling RVFV outbreaks. The identification of suitable epitopes is crucial for the development of safe and effective vaccines.